Rural E-commerce and air pollution: evidence of dual mechanisms from production inputs and supply-chain expansion - Hu, Jingbang; Yin, Guojun (Frontiers in Environmental Science, 2026)
IntroductionRural e-commerce is reshaping agricultural production and circulation in China, improving market access but also raising concerns about its environmental impact. Whether its rapid expansion improves or worsens air quality remains unclear.MethodsUsing county-level data from 2011 to 2021, this study exploits the staggered rollout of the E-commerce into Rural Areas Comprehensive Demonstration (RECD) program and applies a multi-period Difference-in-Differences model to estimate the policy’s effect on PM2.5 concentrations.ResultsThe RECD policy significantly increases PM2.5 levels. Further analysis shows two channels: intensified agricultural inputs and expanded logistics and warehousing. The effect is strongest in regions with higher agricultural dependence, better terrain accessibility, and higher initial levels of economic development and e-commerce.DiscussionRural e-commerce improves market efficiency but also introduces environmental risks by altering production and circulation patterns. Strengthening green technologies, clean logistics and environmental regulation is essential to ensure a sustainable rural digital transformation.